Hvad er religion i Danmark 2014? - Reeh, Niels (Religionsvidenskabeligt Tidsskrift, 2015)
By an analysis of the Danish Humanist Society and the Danish Atheist Society, the aim of this contribution is to consider one aspect of the borderland of the Danish model of religion. On the basis of a relational approach to the study of religion, I conclude that the Humanist Society from an analytical point of view is a religion while the Atheist Society is not. In this manner, the Humanist Society should be regarded as part of the Danish model of religion while the Atheist Society should not. Therefore, it may be argued that the borderland of the Danish model of religion is located between these two organisations. Dette bidrag undersøger en del af den danske religionsmodels grænseflade gennem en analyse af foreningerne Dansk Humanistisk Samfund og Ateistisk Selskab. På baggrund af et relationelt religionsbegreb konkluderes det, at Humanistisk Samfund analytisk set er en religion og dermed en del af den danske religionsmodel. Med hensyn til Ateistisk Selskab konkluderer analysen, at denne forening analytisk set ikke er en religion men snarere en religionspolitisk forening. Ateistisk Selskab er dermed ikke en del af den danske religionsmodel. Den danske religionsmodels grænseflade kan dermed siges at befinde sig imellem disse to organisationer